A Polyphasic Characterisation of Tetradesmus almeriensis sp. nov. (Chlorophyta: Scenedesmaceae) - Sara Turiel (MDPI AG, 2021)
The microalga Tetradesmus almeriensis, previously known as Scenedesmus almeriensis, has been isolated and cultivated as a highly productive, fast-growing strain known as a natural source of different products of commercial interest, including bioactive compounds such as lutein. This strain produces up to 40 g·m−2·day−1 of lutein under optimal conditions and is highly recommendable for outdoor production in temperate and warm climates, showing maximal performance at temperatures up to 35 °C with no photo-inhibition taking place with irradiances greater than 1000 μE·m−2·s−1. Morphological and molecular data allow its assignment to the Chlorophycean genus Tetradesmus. The new species can be distinguished from similar Tetradesmus taxa due to its unique combination of features that are seen under light microscopy. We present herein a robust and comprehensive phylogenetic analysis of T. almeriensis, together with several additional Scenedesmaceae species, using a combination of maximum likelihood and Bayesian approaches. Our results confirm T. almeriensis as a distinct species consistently clustering with other Scenedesmaceae.